The Spinning Box: An Innovative Educational Game to Stimulate Early Childhood Development a Single-group Pre-test and Post-test Research Design - Hasani, Ruslan; Putri, Besse Sherly Aulia; Simunati, Simunati; Yulianto, Yulianto; Agussalim, Agussalim; Lorica, Josephine D.; Abas, Hafiza; Shiratuddin, Mohd Fairuz (IJECA (International Journal of Education and Curriculum Application), 2025)
Early childhood is a critical period for cognitive development, socialization and independence, motor skills, and language. This article introduces the Spinning Box, an innovative educational game designed to stimulate children's holistic development through gross motor skills, fine motor skills, speech and language skills, and socialization and independence. The research method is a quasi-experimental study using a single-group pre-test and post-test design proposed to evaluate its effectiveness. Analysis was descriptive and used paired t-tests to detect differences in mean scores before and after the intervention. Participants consisted of four children aged 3–4 years. Inclusion criteria: healthy children without major developmental disorders, with parental consent. The Spin Box consists of a cube with four sides, each corresponding to a developmental task (motor skills, speech and language skills, and socialization and independence skills). Children took turns spinning the box and completing the assigned tasks. Sessions lasted for 20 minutes, three times a week, for eight weeks. Measurements were conducted using the Pre-Screening Developmental Questionnaire. The results showed significant improvements in all four domains of child development following the Spinning Box intervention. All p-values were below 0.05. Furthermore, Cohen's d effect sizes across all domains were very large (d > 0.8), with most even far exceeding this value. This shows that the Spinning Box educational game has a very strong influence in stimulating development in early childhood. However, with only four participants from one center and a single-group pre-post design, these findings are preliminary and should be interpreted with caution, as they cannot be broadly generalized.Parental involvement is widely recognized as a key determinant of children’s academic achievement, motivation, and socio-emotional development. Yet despite decades of research, evidence on concrete and scalable strategies remains fragmented. This study synthesizes recent innovations by conducting a structured literature review of 63 Scopus-indexed articles published between 2020 and 2025, complemented by earlier foundational works to provide historical and conceptual grounding. The objective was to identify effective approaches, examine barriers to implementation, and highlight emerging opportunities for strengthening parent–school partnerships in primary and secondary education. Findings converge into five clusters. First, programmatic interventions such as parenting workshops and structured sharing sessions enhanced parental knowledge, confidence, and collaboration with teachers, leading to improvements in children’s learning outcomes. Second, technology-enabled access—including internet provision, device distribution, and digital platforms—expanded opportunities for engagement, although inequalities in digital literacy and access remained evident. Third, multi-channel communication systems such as logbooks, bulletins, and social media groups supported continuous dialogue between home and school, with positive effects on student behavior and motivation. Fourth, shared governance through parental participation in school committees, decision-making, and community events fostered inclusivity, reduced dropout risks, and enhanced school–community relationships. Fifth, targeted outreach, including home visits and culturally responsive practices, proved especially effective in reaching disadvantaged families and improving trust, equity, and sustained participation. Overall, the review demonstrates that parental involvement is highly adaptable and can be strengthened through a mix of low-cost innovations and contextually sensitive strategies. These findings offer educators and policymakers actionable insights for institutionalizing parental engagement and addressing persistent equity gaps in education.